2011
DOI: 10.1158/0008-5472.can-10-2493
|View full text |Cite
|
Sign up to set email alerts
|

IRF8 Regulates Acid Ceramidase Expression to Mediate Apoptosis and Suppresses Myelogeneous Leukemia

Abstract: IFN regulatory factor 8 (IRF8) is a key transcription factor for myeloid cell differentiation and its expression is frequently lost in hematopoietic cells of human myeloid leukemia patients. IRF8-deficient mice exhibit uncontrolled clonal expansion of undifferentiated myeloid cells that can progress to a fatal blast crisis, thereby resembling human chronic myelogeneous leukemia (CML). Therefore, IRF8 is a myeloid leukemia suppressor. Whereas the understanding of IRF8 function in CML has recently improved, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 50 publications
1
54
1
Order By: Relevance
“…In murine models, IRF-8 inhibits BCR-ABL ϩ cell proliferation by inducing expression of genes such as Cdkn4b, Blimp-1, and Mets-1 (36,37). IRF-8 also promotes apoptosis by repressing transcription of anti-apoptotic genes such as BCL2 and ASAH1 (21,38). In addition, IRF-8 suppresses WNT/␤-catenin signaling, which has been implicated in the development of CML (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine models, IRF-8 inhibits BCR-ABL ϩ cell proliferation by inducing expression of genes such as Cdkn4b, Blimp-1, and Mets-1 (36,37). IRF-8 also promotes apoptosis by repressing transcription of anti-apoptotic genes such as BCL2 and ASAH1 (21,38). In addition, IRF-8 suppresses WNT/␤-catenin signaling, which has been implicated in the development of CML (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…An interaction between WT1 and STAT3 has been reported; it is possible that WT1 and STAT5 could similarly act to regulate IRF-8 expression (42). Alternatively, Hu et al (38) have demonstrated that the IRF-8 promoter is methylated in CML cell lines and primary blasts, resulting in decreased expression. Thus, FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…10,27 This mechanism is defective in CML leukemic cells that exhibit reduced IRF8 expression, rendering them resistant to apoptosis. 10 Our observation that IRF8-deficient mice accumulate CD11b In conclusion, our ability to separate oligopotent GMPs from their lineage-committed progeny has revealed that IRF8 regulates neutrophil and monocyte production independently in lineage-committed progenitors (GPs and MPs), rather than acting in oligopotent GMPs to instruct monocytic fate. This progenitor isolation approach will also ) were isolated from bone marrow and their morphology was assessed using May-Grünwald Giemsa staining.…”
Section: Cd34mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In humans, IRF8 mutations are associated with immunodeficiency, and decreased IRF8 expression has been observed in both acute myelogenous leukemia (AML) and CML patients. [10][11][12] Previous studies have shown that IRF8 promotes monocyte and DC production but limits neutrophil production. 1,4,[6][7][8][13][14][15] Thus, it is widely thought to act in oligopotent progenitors (common myeloid progenitors [CMPs], and/or granulocyte-monocyte progenitors [GMPs]) to instruct the adoption of monocyte/DC fate and suppress granulocyte fate.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that suppressing IRF8 expression by BCR-ABL involves STAT5 and Irf8 promoter DNA methylation in primary CML cells and in BCR-ABL-positive cell lines [75,76]. On the other hand, in another study that used BCR-ABL-transduced mouse bone marrow progenitor cells, inhibitors of either STAT5 or DNA methylation failed to rescue Irf8 expression [74].…”
Section: As Already Mentioned Irf8mentioning
confidence: 99%